Implementasi Hak Konstitusional Pekerja Mendapatkan Dokumen Kependudukan Dari Perkawinan Tidak Tercatat Di Kelurahan Industri Tenayan: Penelitian - Andrizal; Eddy Asnawi; Tatang Suprayoga; Bambang Hermanto; Zulhian Sultan Javari (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2026)
Registration of marriages under positive law in Indonesia is an administrative obligation of the state to guarantee the protection and fulfillment of human rights. However, in the Industrial Tenayan Village, Pekanbaru City, a group of casual laborers on a palm oil plantation from Nias Regency lack adequate population documents due to their unregistered marital status. The research method used is sociological law with an empirical approach. The results show that the policy transformation through Presidential Regulation No. 96/2018 brought a legal breakthrough in the form of the Absolute Responsibility Statement Letter (SPTJM), which facilitates the inclusion of unregistered married couples' status on Family Cards (KK) and the issuance of birth certificates for children. However, this implementation is hampered by the socio-economic factors of migrant workers, strict work schedules, the lack of original documents, and residents' psychological fear of administrative bureaucracy.